China's borderlands under the Qing, 1644-1912 : perspectives and approaches in the investigation of imperial boundary regions - McMahon, Daniel (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This book explores new directions in the study of China's borderlands. In addition to assessing the influential perspectives of other historians, it engages innovative approaches in the author's own research. These studies probe regional accommodations, the intersections of borderland management, martial fortification, and imperial culture, as well as the role of governmental discourse in defining and preserving restive boundary regions. As the issue of China's management of its borderlands grows more pressing, the work presents key information and insights into how that nation's contested fringes have been governed in the past"--
Perspectives in North American Research on Qing China's frontiers -- Were the Miao Kings "Prophets of Renewal"? The case of the 1795-1797 Hunan Miao revolt -- The middle ground, "middle ground moments," and accommodation in the study of later Qing borderland history -- Geomancy and walled fortifications on a late eighteenth-century Qing borderland -- Fortified walls and social ordering in Qing China's early Jiaqing borderland revolts -- Treachery at imperial edges: criminality and bureaucratic classification as jian in middle Qing China -- Marking "men of iniquity": imperial purpose and imagined boundaries in the Qing processing of rebel ringleaders, 1786-1828.
OCLC-licensed vendor bibliographic record.
Keywords: China -- History -- Qing dynasty, 1644-1912.; China -- Boundaries -- History -- 18th century; China -- Boundaries -- History -- 19th century; China -- Ethnic relations -- History -- 18th century; China -- Ethnic relations -- History -- 19th century; SOCIAL SCIENCE / Ethnic Studies / General; SOCIAL SCIENCE / Research